Factors related to Gaming addiction in adults - C. Neily; M. Maalej; I. Gassara; R. Feki; N. Smaoui; L. Zouari; A. Zouari; J. Ben Thabet; S. Omri; N. Charfi; M. Maalej (European Psychiatry, 2022)
Introduction With the advancement of technology over the last years, gaming is no longer reserved to adolescents. It has become a growing phenomenon within young adults which should,’t be overlooked as it is accompanied with the risk of addiction.